Improving Student Learning Outcomes through the Implementation of the Make A Match Cooperative Learning Model in Islamic Education Learning at SD Negeri 23 Bandar Baru - Liamiswaddah; Alaida, Rafika (Journal of Indonesian Primary School, 2025)
This study aims to test the effect of implementing the Make A Match cooperative learning model on student learning outcomes in Islamic Religious Education subjects at SD Negeri 23 Bandar Baru. This study used a quasi-experimental design with two groups, namely the experimental group that implemented the Make A Match model and the control group that used traditional teaching methods. The results showed that the experimental group experienced a significant increase in their learning outcomes, both in terms of understanding the material and retention of important concepts in Islamic Religious Education. In addition, based on the learning interest questionnaire, students in the experimental group also showed increased engagement and higher motivation during learning. Further classroom observations confirmed these findings, where students in the experimental group were more active in discussing and collaborating with their classmates. This study suggests that implementing the Make A Match model can improve student learning outcomes and engagement in Islamic Religious Education learning, and can be an effective alternative to traditional teaching methods.